Analisis Pendapatan Pedagang Bunga Hias di Kelurahan Kakaskasen Kota Tomohon - Licky N. Rapar; Celsius Talumingan; Esry O.H. Laoh; Eyverson Ruauw (COCOS, 2014)
ABSTRACTThe objective of this study is to determine the income and the efficiency of Ornamental Flower Merchants in the Village of Kakaskasen, Tomohon City. This research is conducted in Kakaskasen Village, Tomohon City for 2 (two) months in November to December 2012. The data used is primary data obtained through direct observation and interviews with Ornamental Flower mercahants based on a questionnaire in the form of questionnaires, and secondary data obtained from the relevant agencies Agriculture Department, the Central Statistics Agency (BPS) Tomohon and Kakaskasen Village Office. The data were analyzed descriptively and presented in tabular form. The results showed that the income of Ornamental Flower Merchants in the Village of Kakaskasen Tomohon City in one production process is Rp 6,694,673.61 /merchant and Rp 18,093,712.46/hectare. The efficiency of the Ornamental Flower Businesses from the R : C Analysis show value greater than one that is 4.29. This indicates that the Ornamental Flower Businesses in Kakaskasen Village Tomohon City is profitable, so it deserves to remain manageable even more developed.Key Word : the income of ornamental flower merchants, the R : C Analysis